How to deal with inequality: Welfare system challenges and European responses - Andreas Friedl; Dennis Görlich; Sebastian Horn; Christiane Krieger-Boden; Matthias Lücke (Kiel Institute for the World Economy (IfW), 2015)
[Introduction ...] In this paper, we seek to identify innovative ways to limit inequality in households' disposable incomes and living standards while keeping welfare systems fiscally sustainable. We focus on the welfare systems of EU countries in comparison, to better understand their key features. To set the scene, we review trends in income inequality in Europe in relation to other major world regions. We compare inequality before and after taxes and transfers across European countries to gain insights into the extent of redistribution and, hence, the impact of the national welfare systems (Section 2). Next we review the experience of five European countries that have been identified as examples of distinct welfare system models. We characterize national welfare systems in terms of the extent to which they decommodify labour, emphasize or relax stratification, and engage in social investment rather than income replacement during spells of unemployment (Section 3). We go on to assess the performance of our selected countries in terms of income redistribution, economic growth, polarization between rich and poor, and labour market developments (Section 4). We complement the picture by looking closely at evidence from surveys and economic experiments to assess inequality aversion in our selected countries and relate our findings to the extent of redistribution and other features of the national welfare systems (Section 5). We look for recent challenges for and responses by the welfare systems and reflect on adjustment requirements that lie ahead (Section 6). The final section concludes (Section 7). [...]
Keywords: 330